High Carriage of tetA, sul1, sul2 and blaTEM Resistance Genes among the Multidrug-resistant Uropathogenic Escherichia coli (UPEC) Strains from Malaysian Patients - Jia-Jin Chin; Hui-Mei Lee; Shuet-Yi Lee; Yin-Ying Lee; Choy-Hoong Chew (Tropical Life Sciences Research, 2024)
The rapid emergence of multidrug-resistant (MDR) uropathogenic Escherichia coli (UPEC) strains pose a critical challenge in urinary tract infection (UTI) treatments. However, little work elucidated the resistance mechanisms of the MDR UPEC clinical strains in Malaysia. Therefore, this study aimed to determine the antimicrobial susceptibility profiles and the prevalence of antimicrobial resistance genes among the UPEC strains. Polymerase chain reactions were conducted to detect the presence of 6 antimicrobial resistance genes among 60 UPEC strains. Meanwhile, the antimicrobial resistance profiles against 9 antimicrobials were examined through the Kirby-Bauer disk diffusion method. In this study, the MDR isolates accounted for 40.0% (24/60), with the highest prevalence of resistance towards ampicillin (43/60; 71.7%), followed by tetracycline (31/60; 51.7%), nalidixic acid (30/60; 50.0%), co-trimoxazole (20/60, 33.3%), ciprofloxacin (19/60, 31.7%), levofloxacin (16/60, 21.6%) and chloramphenicol (10/60, 16.7%). In contrast, low resistance rates were observed among minocycline (1/60; 1.7%) and imipenem (0/60; 0.0%). blaTEM was the most prevalent gene (36/60; 60.0%), followed by tetA (27/60; 45.0%), sul2 (25/60; 41.7%), sul1 (13/60; 21.7%) and tetB (8/60; 13.3%). Surprisingly, blaSHV was not detected among the UPEC isolates. The MDR, ampicillin and tetracycline-resistant isolates were significantly associated with a higher prevalence of tetA, sul1, sul2 and blaTEM. In contrast, tetB displayed no significant relationship with any of the antimicrobials tested. The patient’s age and gender were not the risk factors for the carriage of the resistance genes. Our findings identified the common resistance genes carried by the antimicrobial resistant UPEC isolates and provide valuable insights into developing the best antibiotic prescription regime to treat UTIs in our local scene.